Outcome of cephalosporin treatment for serious infections due to apparently susceptible organisms producing extended-spectrum beta-lactamases: Implications for the clinical microbiology laboratory - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2001)
Although extended-spectrum beta-lactamases (ESBLs) hydrolyze cephalosporin antibiotics, some ESBL-producing organisms are not resistant to all cephalosporins when tested in vitro. Some authors have suggested that screening klebsiellae or Escherichia coli for ESBL production is not clinically necessary, and when most recently surveyed the majority of American clinical microbiology laboratories did not make efforts to detect ESBLs, We performed a prospective, multinational study of Klebsiella pneumoniae bacteremia and identified 10 patients who were treated for ESBL-producing K. pneumoniae bacteremia with cephalosporins and whose infecting organisms were not resistant in vitro to the utilized cephalosporin. In addition, we reviewed 26 similar cases of severe infections which had previously been reported. Of these 36 patients, 4 had to be excluded from analysis. Of the remaining 32 patients, 100% (4 of 4) patients experienced clinical failure when MICs of the cephalosporin used for treatment were in the intermediate range and 54% (15 of 28) experienced failure when MICs of the cephalosporin used for treatment were in the susceptible range, Thus, it is clinically important to detect ESBL production by klebsiellae or E, coli even when cephalosporin MICs are in the susceptible range (less than or equal to 8 mug/ml) and to report ESBL-producing organisms as resistant to aztreonam and all cephalosporins (with the exception of cephamycins).
Keywords: RESISTANT KLEBSIELLA-PNEUMONIAE; ESCHERICHIA-COLI; CEFTAZIDIME RESISTANCE; MEDICAL-CENTER; OUTBREAK; STRAIN; BACTEREMIA; FAILURE; SHV-5